# SOLUTION: A great thank you to whoever solve the following problem!!! Given that log(base b)(x y^2) = m and log(base b)(x^3 y) = n, express log(base b)(y/x) and log(base b) (x^0.5 y^0.5) i

Algebra ->  Algebra  -> Logarithm Solvers, Trainers and Word Problems -> SOLUTION: A great thank you to whoever solve the following problem!!! Given that log(base b)(x y^2) = m and log(base b)(x^3 y) = n, express log(base b)(y/x) and log(base b) (x^0.5 y^0.5) i      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Logarithm Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on logarithm Question 549638: A great thank you to whoever solve the following problem!!! Given that log(base b)(x y^2) = m and log(base b)(x^3 y) = n, express log(base b)(y/x) and log(base b) (x^0.5 y^0.5) in terms of m and n. Answer by htmentor(789)   (Show Source): You can put this solution on YOUR website!Given that log(base b)(x y^2) = m and log(base b)(x^3 y) = n, express log(base b)(y/x) and log(base b) (x^0.5 y^0.5) in terms of m and n. =============================== For simplification, we will write log(base b) as log Using the rules of logarithms, we can write: log(xy^2) = log(x) + 2log(y) = m [1] log(x^3y) = 3log(x) + log(y) = n [2] We can use these two equations to solve for log(x) and log(y) in terms of m and n: Subtract 1/2 the 1st equation from the 2nd: 3log(x) - 1/2log(x) = n - m/2 5/2log(x) = n - m/2 log(x) = 2/5(n - m/2) = 1/5(2n - m) Now use [2] to solve for log(y): log(y) = n - 3/5(2n - m) -> log(y) = -n/5 + 3m/5 = 1/5(3m - n) (a) log(y/x) = log(y) - log(x) = 1/5(3m - n) - 1/5(2n - m) = 4m/5 - 3m/5 = 1/5(4m - 3n) (b) log(x^0.5 y^0.5) = (1/2)log(x) + (1/2)log(y) = 1/10(2n - m) + 1/10(3m - n) = 1/10(n + 2m)